Attenuated frontal and sensory inputs to the basal ganglia in cannabis users. (3rd March 2016) - Blanco‐Hinojo, Laura; Pujol, Jesus; Harrison, Ben J; Macià, Dídac; Batalla, Albert; Nogué, Santiago; Torrens, Marta; Farré, Magí; Deus, Joan; Martín‐Santos, Rocío
Abstract: Heavy cannabis use is associated with reduced motivation. The basal ganglia, central in the motivation system, have the brain's highest cannabinoid receptor density. The frontal lobe is functionally coupled to the basal ganglia via segregated frontal–subcortical circuits conveying information from internal, self‐generated activity. The basal ganglia, however, receive additional influence from the sensory system to further modulate purposeful behaviors according to the context. We postulated that cannabis use would impact functional connectivity between the basal ganglia and both internal (frontal cortex) and external (sensory cortices) sources of influence. Resting‐state functional connectivity was measured in 28 chronic cannabis users and 29 controls. Selected behavioral tests included reaction time, verbal fluency and exposition to affective pictures. Assessments were repeated after one month of abstinence. Cannabis exposure was associated with (1) attenuation of the positive correlation between the striatum and areas pertaining to the 'limbic' frontal–basal ganglia circuit, and (2) attenuation of the negative correlation between the striatum and the fusiform gyrus, which is critical in recognizing significant visual features. Connectivity alterations were associated with lower arousal in response to affective pictures. Functional connectivity changes had a tendency to normalize after abstinence. The results overall indicate that frontal and sensory inputs to the basal ganglia are attenuated after chronic exposure to cannabis. This effect is consistent with the common behavioral consequences of chronic cannabis use concerning diminished responsiveness to both internal and external motivation signals. Such an impairment of the fine‐tuning in the motivation system notably reverts after abstinence. Abstract : The basal ganglia are central in the motivation system. Using resting‐state fMRI, we examined basal ganglia functional connectivity in 28 chronic cannabis users without comorbid psychiatric disorders and 29 controls. Compared with controls, cannabis users showed abnormal (attenuated) functional coupling of the striatum with converging frontal and sensory cortical areas. Connectivity alterations were associated with lower arousal in response to affective pictures. Our findings suggest that functional changes associated with active cannabis use have a tendency to recover with abstinence.